2020
DOI: 10.1111/hir.12332
|View full text |Cite
|
Sign up to set email alerts
|

A clinical librarian in a hospital critical care unit may generate a positive return on investment

Abstract: Background Timely information provided by clinical librarians can contribute to outcomes such as improved patient care and time savings for hospital staff. What is unknown is the return on investment (ROI) of a clinical librarian on a critical care unit. Objective The aim of this study was to assess the ROI, from the employer perspective, of placing a clinical librarian in a critical care unit in a large UK acute hospital. Methods Using a mixed methods approach, ROI was estimated by comparing the total costs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The findings demonstrate that the wide‐ranging impacts of CLs demonstrated in one region are applicable across the UK. These findings are further supported by a study which examined the work of CLs in an English critical care unit (Hartfiel et al, 2020). The study measured outcomes in relation to time saved, support for professional development and improved care.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The findings demonstrate that the wide‐ranging impacts of CLs demonstrated in one region are applicable across the UK. These findings are further supported by a study which examined the work of CLs in an English critical care unit (Hartfiel et al, 2020). The study measured outcomes in relation to time saved, support for professional development and improved care.…”
Section: Discussionsupporting
confidence: 56%
“…In line with our study, evidence was of impact found in relation to evidence-based practice, and improved clinical decision-making. Crucially this study (Hartfiel et al, 2020) sought to quantify or monetise the benefits of CL services. The qualitative data above suggests that there are cost savings made when using evidence from CL services, but as our study was national and covered wide ranging services provided, these could not be quantified.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the timely provision of information, clinical librarians have been found to positively contribute to improved patient care and time savings for hospital staff. In Hartfiel et al,’s (2021) mixed methods study, they examined the return on investment benefits of introducing a clinical librarian in a critical care unit. Looking at salary and equipment costs in relation to time saved, personal development and improved patient care, Hartfiel et al report a positive ROI of £1.18–£3.03 for every £1 invested.…”
Section: In This Issue…mentioning
confidence: 99%
“…According to the Medical Library Association (USA), "The health information profession provides access to and delivers important information that improves patient care and supports education, research, and publication" [19]. Information services provided by health information professionals have been shown to help mitigate barriers to use of evidence, such as lack of time and inadequate search skills, by providing mediated information retrieval, support for evidence-based practice (EBP) and information literacy (IL) [7,8,[20][21][22][23]. This can take the form of services or Continuing Education (CE) instruction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a clinical librarian has been shown to “affect personal searching behavior as doctors were also prepared to spend longer on searches” [ 24 ]. A recent study has shown that librarian participation in clinical rounds reduces costs [ 21 ], although Madden et al [ 25 ] found that there is a “need for future research to develop standardised, validated tools that clinical libraries can use to demonstrate their financial impact.”…”
Section: Introductionmentioning
confidence: 99%